2023
DOI: 10.31234/osf.io/pcgzd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Introducing Alcohol-Free Beer Options in Bars and Public Houses on Alcohol Sales and Revenue: A Randomised Crossover Field Trial

Katie De-loyde,
Jennifer Ferrar,
Mark Andrew Pilling
et al.

Abstract: Aims. The study aimed to estimate the impact of introducing a draught alcohol-free beer, thereby increasing the relative availability of these products, on alcohol sales and monetary takings in bars and pubs in England.Design. Randomised crossover field trial.Participants. Fourteen venues that did not previously sell draught alcohol-free beer.Intervention. Venues completed two intervention periods and two control periods in a randomised order over 8 weeks. Intervention periods involved replacing one draught al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Household data from Spain highlight that 12% of all beer purchases and 4% of all wine purchases were non-alcoholic, and these purchases were associated with subsequent reduction in full-strength alcohol purchases [10]. A recent UK field trial found that regular-strength beer sales decreased when pubs added a non-alcoholic beer option (with no loss of profits) [11]. However, household purchase data are limited by not capturing all purchases a household makes and, as with the field trial, not directly assessing who is consuming NABs or for what purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Household data from Spain highlight that 12% of all beer purchases and 4% of all wine purchases were non-alcoholic, and these purchases were associated with subsequent reduction in full-strength alcohol purchases [10]. A recent UK field trial found that regular-strength beer sales decreased when pubs added a non-alcoholic beer option (with no loss of profits) [11]. However, household purchase data are limited by not capturing all purchases a household makes and, as with the field trial, not directly assessing who is consuming NABs or for what purpose.…”
Section: Introductionmentioning
confidence: 99%